The Influence of Information Technology and Leadership Commitment to Fixed Asset Management at the Regional Revenue and Asset Agency of Kupang Regency with Inventory as a Moderating Variable - Tanan, Eugenia H. P.; Mudamakin, Agnes K. B.; Khavanzah, Khavanzah (Borong Newinera Publisher, 2026)
Regional Asset Management (BMD) is a crucial element in the implementation of government and public services. However, its practice still faces many obstacles. This study highlights a phenomenon in the Kupang Regency Government, where the Audit Report (LHP) of the Supreme Audit Agency (BPK) for 2018-2022 showed significant problems in the administration of fixed assets, which impacted the Fair with Exceptions (WDP) opinion. The main problem identified was the disorderly inventory of assets. This study aims to examine the effect of Information Technology (X1) and Leadership Commitment (X2) on Fixed Asset Management (Y). In addition, this study also examines whether Asset Inventory (Z) moderates (strengthens or weakens) the relationship between information technology and leadership commitment to fixed asset management. This study uses a quantitative approach with a saturated sample of 88 respondents, consisting of OPD leaders and asset administrators in 44 OPDs of the Kupang Regency Government. Data were analyzed using Structural Equation Modeling (SEM ) based on Partial Least Square (PLS) with SmartPLS 4.0 software. The results of the study show that Information Technology, Leadership Commitment, and Asset Inventory each have a positive and significant effect on Fixed Asset Management.